1891 Mich. Pub. Acts 409 - (:unkn) unknown (My University, 1891)
Police Department, pt 15: Prohibited the carrying of a concealed pistol, revolver, Bowie knife, dirk, slungshot, billie, sandbag, false knuckles, or other dangerous weapon. Also prohibited lurking or being concealed with the intent to injure a person or property, or threatening to beat or kill a person or property. Punishable by fine up to $100 and the costs of prosecution, and in default of payment, imprisonment.
Keywords: CARRY - CONCEALED; CARRY - INTENT TO COMMIT CRIME